Towards the Development of Recreational Fisheries in Kerala - Ramakrishnan Korakandy (Tourism Recreation Research, 1998)
Development of recreational fisheries is currently not on the agenda of academic thinking in fishery scientific circles in Kerala. This paper seeks to establish a case for developing a recreational fishery in Kerala. It has been argued on grounds of potential markets and developmental needs. Optimum use of the natural resource and protection of the ecology and culture of the landscape adjoining the waterside !rom existing environmental hazards are also cited as additional reasons for its development. A strategy for the development of recreational fisheries is suggested.